Seismic activity and an anomalous fumarolic chemical composition due to seal effect in the volcanic system of Deception Island (Antarctica) - Caselli, A.T. (2007)
In this communication, the genesis of great anomalous seismic activity registered during austral summer 2003/2004 on Deception Island (Antarctica) is discussed, and related with changes on the chemical composition of fumarolic gases and vent deposits. Here we present a comparative analysis performed to explain this activity. We propose a possible parcial seal of the microfracture system. This effect allows an increase on pressure follow by reopening of microfractures, resulting on a sequence of seismic events and changes on the chemical composition of fumarolic emissions.